The Hsp70 homolog Ssb affects ribosome biogenesis via the TORC1-Sch9 signaling pathway - Mudholkar, Kaivalya; Fitzke, Edith; Prinz, Claudia; Mayer, Matthias P.; Rospert, Sabine (Nature Communications, 2017)
The yeast Hsp70 homolog Ssb is a chaperone that binds translating ribosomes where it is thought to function primarily by promoting nascent peptide folding. Here the authors find that the ribosome biogenesis defect associated with the loss of Ssb is attributable to a specific disruption in TORC1 signaling rather than defects in ribosomal protein folding.
Gesehen am 24.05.2018